Rational Design of Low Cost and High Energy Lithium Batteries through Tailored Fluorine‐free Electrolyte and Nanostructured S/C Composite. Issue 17 (19th July 2018) - Agostini, M.; Lim, D.‐H.; Sadd, M.; Hwang, J.‐Y.; Brutti, S.; Heo, J. W.; Ahn, J. H.; Sun, Y. K.; Matic, A.
Abstract: We report a new Li–S cell concept based on an optimized F‐free catholyte solution and a high loading nanostructured C/S composite cathode. The Li2 S8 present in the electrolyte ensures both buffering against active material dissolution and Li + conduction. The high S loading is obtained by confining elemental S (≈80 %) in the pores of a highly ordered mesopores carbon (CMK3). With this concept we demonstrate stabilization of a high energy density and excellent cycling performance over 500 cycles. This Li–S cell has a specific capacity that reaches over 1000 mA h g −1, with an overall S loading of 3.6 mg cm −2 and low electrolyte volume (i.e., 10 μL cm −2 ), resulting in a practical energy density of 365 Wh kg −1 . The Li–S system proposed thus meets the requirements for large scale energy storage systems and is expected to be environmentally friendly and have lower cost compared with the commercial Li‐ion battery thanks to the removal of both Co and F from the overall formulation. Abstract : New system in town : A new Li–S cell concept based on an optimized F‐free catholyte solution and a high loading nanostructured C/S composite cathode is demonstrated with practical energy densities superior to commercially available Li‐ion systems. The Li–S system meets the requirements for large scale energy storage systems and is expected to be environmentally friendly and have lower cost compared with the commercial Li‐ion batteries.